МОДЕЛЬ ОСОБИСТОСТІ СУЧАСНОГО ВЧИТЕЛЯ І її ФОРМУВАННЯ В УМОВАХ ВИЩОЇ ШКОЛИ (Педагогіка вищої та середньої школи, 2007)
The paper deaals witv the grounding of the structural pattern of modern teacher personality as well as the conditious of its successful realisation in higher school educational process.